Why do larger mothers produce larger offspring? A test of classic theory. Issue 12 (2nd December 2016) - Cameron, Hayley; Monro, Keyne; Malerba, Martino; Munch, Stephan; Marshall, Dustin
Abstract: Across a wide range of taxa, larger mothers produce larger offspring. Theory assumes that larger, more fecund mothers create higher local densities of siblings, and so larger mothers produce larger offspring to offset sibling competition. This assumption has been debated for over 30 yr, but direct empirical tests are surprisingly rare. Here, we test two key assumptions of classic theories that predict sibling competition drives maternal‐size–offspring‐size (MSOS) correlations: (1) independent effects of offspring size and sibling density on offspring performance or (2) as a product of an interaction between these two factors. To simultaneously test these alternative assumptions, we manipulate offspring size and sibling density in the marine invertebrate, Bugula neritina, and monitor offspring performance in the field. We found that, depending on the fitness metric being considered, offspring size and sibling density can either independently or interactively affect offspring performance. Yet sibling density did not affect offspring performance in the ways that classic theories assume. Given our results, it is unlikely that sibling competition drives the positive MSOS correlation observed in this species. Empirical support for these classic theories remains lacking, suggesting alternative explanations are necessary.